In vitro Maturation of Oocytes from Santa Ines Ewes Subjected to Consecutive Sessions of Follicular Aspiration by Laparoscopy - Padilha, L. C. [UNESP]; Teixeira, P. P. M. [UNESP]; Pires-Buttler, E. A. [UNESP]; Apparicio, M. [UNESP]; Motheo, T. F. [UNESP]; Savi, P. A. P. [UNESP]; Nakaghi, E. Y. O.; Alves, A. E. [UNESP]; Vicente, W. R. R. [UNESP] (Wiley-Blackwell, 2014)
Contents The success of embryo production in vitro depends upon the use of an efficient oocyte retrieval technique, and the best results have been obtained by laparoscopic aspiration. The aim of this study was to evaluate the effect of consecutive sessions of follicular aspiration on the quantity, quality and in vitro maturation competence of oocytes obtained from ewes subjected to hormonal stimulation. Six Santa Ines ewes underwent nine sessions of follicular aspiration by laparoscopy with a 7-day interval between sessions, totalling 56 aspirations. After 24h of culture, oocytes were stained and classified according to the stage of nuclear and cytoplasmic maturation. Oocyte retrieval rate was 61.4 +/- 2%, resulting in a total of 249 oocytes. No significant variation was observed between sessions (p>0.05). The average number of oocytes retrieved from each ewe was 6.4 +/- 2 per session and 42 +/- 4 in total. No significant difference was observed between the frequencies of the different stages of nuclear maturation: 32.72% mature, 40.74% immature and 26.54% degenerated/indeterminate oocytes; however, a significant difference was observed between the frequencies of the different stages of cytoplasmic maturation: 10.7% mature, 73.25% immature and 16.05% degenerated/indeterminate oocytes. No significant difference was observed in nuclear or cytoplasmic maturation between the weeks of procedure. We conclude that after nine consecutive sessions of follicular aspiration, the quantity and quality of retrieved oocytes remained unchanged as well as the levels of nuclear and cytoplasmic maturation obtained, demonstrating the viability of this technique for repetitive follicular aspirations on the same donor.